Computer alienation behaviour on secondary schools students in Malacca Valley / Farah Syazwani Mohamed Rashid - Mohamed Rashid, Farah Syazwani (2017)
Computer addiction or today known as computer alienation is a dependence on the use of computer device (especially laptops, desktop computers, smartphone) to the typical symptoms of addictive behaviours. The relationship between common problematic computer device use and factor of addiction among students in secondary school have been famous nowadays. Using the computer device should be controlled in order to prevent problems in the future, as will the uncontrollable consumption caused a variety of problems in terms of academic, social, and psychological. This study aims (1) to identify the existence of Computer Alienation (CA) by gender among students in the Secondary Schools in Malacca Valley, (2) to measure the level of alienation behaviour among students in the Secondary Schools in Malacca Valley and (3) to determine the main factors that can trigger the students to engage to the Computer Alienation (CA) behavior. The study was conducted in three secondary schools located in Malacca, Malaysia. A total of 300 of one to five grade students from the selection of school is made up of three types of secondary schools, the high school girls, high school boys and high school boys and girls mix. Drawn from this review, a conceptual framework consisting of four factors influencing computer alienation behaviour has been formulated. This conceptual framework serves as a research design to investigate the factors that influence computer alienation behaviour among students in the Secondary Schools in Malacca Valley.